Signaling Pathways and Therapeutic Strategies in Advanced Basal Cell Carcinoma - Vallini, Giulia; Calabrese, Laura; Canino, Costanza; Trovato, Emanuele; Gentileschi, Stefano; Rubegni, Pietro; Tognetti, Linda (Cells (Basel, Switzerland), 2023)
Non-melanoma skin cancers (NMSCs) are the most common human neoplasms world-wide. In detail, basal cell carcinoma (BCC) is the most frequent malignancy in the fair-skinned population. The incidence of BCC remains difficult to assess due to the poor registration practice; however, it has been increasing in the last few years. Approximately, 85% of sporadic BCCs carry mutations in Hedgehog pathway genes, especially in PTCH, SUFU and SMO genes, which lead to the aberrant activation of GLI transcriptional factors, typically silent in cells of adult individuals. The management of advanced BCC (aBCC), both metastatic (mBCC) and locally advanced BCC (laBCC), not candidates for surgical excision or radiotherapy, remains challenging. The discovery of mutations in the Hh signaling pathway has paved the way for the development of Hh pathway inhibiting agents, such as vismodegib and sonidegib, which have represented a breakthrough in the aBCC management. However, the use of these agents is limited by the frequent occurrence of adverse events or the development of drug resistance. In this review, we thoroughly describe the current knowledge regarding the available options for the pharmacological management of aBCCs and provide a forward-looking update on novel therapeutic strategies that could enrich the therapeutic armamentarium of BCC in the near future.